Information needs of Malaysian parents of children with cancer: a qualitative study - Tan, Chai Eng; Lau, Doris Sie Chong; Abdul Latiff, Zarina; Lee, Chee Chan; Teh, Kok Hoi; Mohd Sidik, Sherina (Elsevier, 2022)
Objective: Informational support is an important pillar of psychosocial care for parents of children with cancer. Understanding the information needs of these parents may improve the provision of family-centered informational support. This paper aims to explore the information needs of Malaysian parents whose children have cancer. Methods: This qualitative study was conducted among 14 parents of children with cancer and 8 healthcare providers. The parents were recruited from two urban pediatric oncology centers in Malaysia. Healthcare providers were recruited from these centers, as well as from community-based palliative care providers. In-depth interviews were conducted based on semi-structured topic guides, audio-recorded, and transcribed for thematic analysis using elements of the grounded theory approach. Results: Analysis revealed three themes of information needs, which were: “interaction with the healthcare system,” “care for the child at home” and “psychosocial support for parents”. Information needs on parents’ interaction with the healthcare system consisted of disease and treatment-related information, as well as health system navigation. Information needs on care for the child at home were represented by their caregiving for basic activities of daily living, medical caregiving, and psychosocial caregiving. Psychosocial support for parents included information on practical support and self-care. There were differences in priorities for information needs between parents and healthcare providers. Conclusions: Meeting the information needs of parents is an important part of psychosocial care in pediatric cancer care. Informational support may empower parents in caregiving for their child. The development of suitable information resources will be invaluable for healthcare providers in supporting parents’ needs.